Kajian Etnosains Dalam Proses Pembuatan Tempe Gembus Dalam Pembelajaran IPA - Ananda, Mia Lisy; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2025)
Local wisdom in society is rich in indigenous scientific knowledge. However, the reconstruction of original science in society into scientific science is still very limited. This research is based on the limited reconstruction of original science that developed in society into scientific science that can be used by students as an independent learning resource. Research on